SCHIZOPHRENIC CULTURE: CHALLENGES IN POSTMODERN ARCHITECTURE - Prayitno, Aryasatya Rafa (Border: Jurnal Arsitektur, 2025)
Architecture continuously evolves alongside humanity, with postmodernism representing a critical phase that introduces complex challenges. Central to this discussion is the notion of schizophrenic culture—a concept borrowed from Fredric Jameson, which describes a cultural condition marked by fragmentation, depthlessness, and the collapse of coherent meaning, often found in postmodern societies. This research aims to critique postmodernism in the context of increasing commercialization and its impact on architectural practice. By employing a qualitative-reflective methodology, data were collected through in-depth interviews and analyzed using NVivo software, complemented by formal logic. The study highlights significant projects, such as The Line in Saudi Arabia, which illustrate the tension between commercial growth and the preservation of cultural identity. Findings reveal that while commercialization can drive innovation, it also poses a risk of homogenizing architectural designs, undermining the diverse cultural expressions that postmodernism seeks to champion. Ultimately, this research advocates for a re-evaluation of how economic objectives can coexist with the foundational principles of postmodernism, providing critical insights and recommendations for future studies to navigate the challenges posed by commercialization within the architectural field.